Optically switchable photonic metasurfaces - Waters, R. F. (2015)
We experimentally demonstrate an optically switchable gallium-based metasurface, in which a reversible light-induced transition between solid and liquid phases occurring in a confined nanoscale surface layer of the metal drives significant changes in reflectivity and absorption. The metasurface architecture resonantly enhances the metal's “active plasmonic” phase-change nonlinearity by an order of magnitude, offering high contrast all-optical switching in the near-infrared range at low, μW μm−2, excitation intensities.